Urgensi Pemilih Millenial dalam Pengawasan Pemilu 2024 - Muhamad Arif Setiawan; Rahmah Meladiah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Elections are a process of changing the leadership relay that is routinely carried out in a democratic country, the result of elections is to give birth to leaders who have been elected by the people who exercise their right to vote when elections are held. In the current modern era, elections in Indonesia are decorated by the majority of millennial voters in its implementation, millennial voters have an active tendency when participating in elections, millennial voters also have the potential to have more enthusiasm when making their choices. But of all the stories about the election, supervision is one thing that cannot be forgotten, millennial voters must also take a role in monitoring it, because intense and maximum supervision will make the election clean. Seeing the potential possessed by millennial voters, we must maximize the urgency of millennial voters in supervising the upcoming 2024 elections. If you look at the current phenomenon with the widespread use of media as the main instrument in life activities, millennial voters can take advantage of the potential of digital media to carry out surveillance if there are forms of election violations that occur in the field. Millennial voters can make big moves through their media by making the fraudulent acts viral and taking advantage of the facilities provided by Bawaslu through the election monitoring application.